THE EFFECT OF DIFFERENT COLOUR LEDS ON DATA TRANSMISSION - Salihah Tan Shilan; Syamil Md Noor; Nor Zaity Zakaria; Farah Najihah Razali (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Visible light communication (VLC) is a communication method where light is utilized as a medium of communication for data transmission. VLC is also regarded as a viable technique for indoor applications, assisting Wi-Fi to handle the spectrum crunch. This study aims to investigate the effect of different LED colours towards the distance and efficiency of data transmission with solar panels as a receiver. The experiment entailed gathering and inspecting components such as Arduino UNOs, solar panels, and LEDs, as well as replacing damaged or poorly kept ones to ensure correct operation and efficient debugging. A program was uploaded to the Arduino UNO boards to handle data transmission, including noise cancellation and ensuring synchronisation. Red, yellow and green LEDs are used as a transmitter light source. The experiment was conducted in a dark room as minimum ambient light noise is required to ensure accurate results. The study concluded that red colour LED could transmit the data at a longer distance than the other two colours but with low efficiency. It shows that light intensity and light sensitivity of the solar panel play a crucial role in data transmission performance.